2018
DOI: 10.3389/fimmu.2018.02084
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1-LFA-1 Dependent CD8+ T-Lymphocyte Aggregation in Tumor Tissue Prevents Recirculation to Draining Lymph Nodes

Abstract: The quantity of T-lymphocytes reaching the draining lymph nodes from tumors is likely important to mount effective distant responses and for the establishment of long term systemic memory. Looking into mechanisms behind lymphocyte egress, we directed our attention to leukocyte adhesion mechanisms inside tumors. Here we demonstrate that activated T-cells form intra-tumor aggregates in a LFA-1-ICAM-1-dependent fashion in mouse models of melanoma and breast cancer. We also provide evidence of the presence of T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…In addition to T cell migration into tumors, T cells must also be able to recirculate from the tumor site to draining lymph nodes in order to mount distant responses (134). Interestingly, Yanguas et al showed that in a mouse model of melanoma, increased number of intra-tumorally injected tumor-specific T cells migrated into the draining lymph nodes in mice treated with anti-ICAM-1 or anti-LFA-1 mAbs compared to mice treated with control IgG (134). Further, activated T cells formed intra-tumoral clusters mediated by LFA-1/ICAM-1 interactions in mouse models of melanoma and breast cancer and similar T cell clusters were also visible in primary human melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to T cell migration into tumors, T cells must also be able to recirculate from the tumor site to draining lymph nodes in order to mount distant responses (134). Interestingly, Yanguas et al showed that in a mouse model of melanoma, increased number of intra-tumorally injected tumor-specific T cells migrated into the draining lymph nodes in mice treated with anti-ICAM-1 or anti-LFA-1 mAbs compared to mice treated with control IgG (134). Further, activated T cells formed intra-tumoral clusters mediated by LFA-1/ICAM-1 interactions in mouse models of melanoma and breast cancer and similar T cell clusters were also visible in primary human melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that ICAM-1 in the vascular endothelium was associated with T cell migration, and ICAM-1 expression was upregulated in lymphatic vessels and blood vessels in an inflammatory microenvironment, which promoted T cell migration and inflammatory responses [ 31 33 ]. Based on the inhibition of ICAM-1 expression mediated by miR-223, we further evaluated whether miR-223 could affect T cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…LFA-1 also interacts with intercellular adhesion molecules 1 (ICAM-1), which is related to cancer [6] . It was shown that disrupted LFA-1-ICAM-1 interaction in cancer models increases the presence of activated CD8+ T cells he incidence of tumor- draining lymph nodes [7] . Thus, LFA-1/ICAM-1 pathway plays an important role in in the protection from infections and cancer via activation and function of T cell trafficking [8] .…”
Section: Discussionmentioning
confidence: 99%